HISTORICAL REALITY AND ARTISTIC PLOT IN THE FIRST UZBEK TETRALOGY "THE GREAT REIGN" (Archive of Conferences, 2020)
In this article, the talented writer Muhammad Ali describes the psychological traits in the first part of the tetralogy "The Great reign" in the book Jahongir Mirzo. It explores the chronology of news, the principles of artistic conflict and the psychological picture, as well as how researchers from all over the world and Uzbekistan react. The wonderful pain and sadness surrounding the soul of the wonderful Jahongir Mirzo give a beautiful illustration of his great and infinite love. The concept of the great son of Amir Temur, who has his own philosophical views on love and life, is very complex in the tetralogy. In particular, Amir Temur's views on the father in the election of the bride became famous. Textual analysis of the types of artistic conflicts also helped to establish the scientific and theoretical value of the author's principles. Some notable emphasis was also placed on the concept of a well-connected plot and composition. In particular, the psychological tension between time A and time B proved to be a convincing manifestation of the author's fiction. From the point of view of historical reality, it was revealed that various realities in a work of art are the product of creative intent